Exploring the construction of a Bronze Age braided band from Dartmoor, UK - Elliott-Minty, Celia (Archaeological Textiles Review, 2020)
During the excavation of a Bronze Age cremation on Dartmoor, Devon (UK), the remains of a braided band of cow hair with metallic studs were found. A study of the braid structure was made using magnified digital images. Braiding was carried out with tail hair from two heritage breeds of cattle, using construction methods considered the most appropriate, given the age of the braid. Comparison of both the practicalities of the braiding process and the resultant structures leads to a conclusion that loop manipulation was the most likely method of production of this artefact in the Bronze Age although free-end braiding remains a possibility.